Gamma irradiation resistance of an early age slag-blended cement matrix for nuclear waste encapsulation. Issue 9 (3rd February 2015) - Mobasher, Neda; Bernal, Susan A.; Kinoshita, Hajime; Sharrad, Clint A.; Provis, John L.
Abstract: Abstract : Irradiation is one of the characteristic conditions that nuclear wasteforms must withstand to assure integrity during their service life. This study investigates gamma irradiation resistance of an early age slag cement-based grout, which is of interest for the nuclear industry as it is internationally used for encapsulation of low and intermediate level radioactive wastes. The slag cement-based grout withstands a gamma irradiation dose of 4.77 MGy over 256 h without reduction in its compressive strength; however, some cracking of irradiated samples was identified. The high strength retention is associated with the fact that the main hydration product forming in this binder, a calcium aluminum silicate hydrate (C–A–S–H) type gel, remains unmodified upon irradiation. Comparison with a heat-treated sample was carried out to identify potential effects of the temperature rise during irradiation exposure. The results suggested that formation of cracks is a combined effect of radiolysis and heating upon irradiation exposure.